Efficacy Of Pimozide In Delusion Of Parasitosis - Chakraborty Kalyan; Roy Aloke Kumar (Wolters Kluwer Medknow Publications, 1998)
Twenty patients of dulusion of parasitosis received oral pimozide (PMZ) 2 mg daily for 3 months. Trihexyphenydyl hydrochloride (THP) was administered in a dose of 4 mg daily in young adults and 2 mg daily in elderly patients for prevention of extrapyramidal side effects (EPS). Within 1-2 week of initiation of therapy, sixteen patients responded completely. In four patients, dosage of PMZ had to be increased to 4 mg daily and they responded 3-4 week after initiation of therapy. Treatment was continued for 3 months and all were symptom free. Following discontinuation of therapy, delusion reappeared but disappeared after reinstitution of PMZ therapy. EPS developed in two young patients resulting in discontinuation of pimozide.